Design and development of intelligent electronic tutorial software for GSM maintenance in Nigeria - Nwabueze, Ekwonwune Emmanuel; Ngozi, Nwachukwu Catherine Ada; Obiageli J., Anyaduba; Fortune, Obikwere (Journal of Advanced Computer Science & Technology, 2015)
The Global System of Mobile communication (GSM) technology has permeated every facet of human existence ,that man can no longer do away with it. This piece of work was motivated by the nagging problems, which include poor quality of service by telecom service providers, which attempts to negate the value of this revolution, inaccurate and interrupted service delivery which have resulted to delayed and aborted calls, traffic congestion, low bandwidth and oversubscription errors, inter alia. So the primary objective of this article therefore, is to design and develop intelligent electronic tutorial GSM software that would be capable of providing relevant answers to some GSM-based service challenges raised above. The Structured Systems Analysis and Design Methodology (SSADM) was employed as research methodology. The expected results shall include, among others, broadened scope of knowledge in GSM tutorial software engineering, provision of user friendly environment and cost effective communication system for a happy customer and a better society; provide an effective and feasible solution for a reliable and accurate GSM management system that would improve the efficiency and productivity of Nigerian information and communication infrastructure.